TAMAN EDUKASI URBAN FARMING DI BANJARBARU - Sukmajaya, Natha Lalita; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Currently, urban farming is increasingly developing because the problem of decreasing agricultural land in urban areas is increasing, which can affect urban food security. This problem encourages people to utilize and optimize the potential of surrounding resources to cultivate food and livestock on limited land and abandoned urban areas to the fullest. In recent years, urban farming has also increasingly developed in the city of Banjarbaru, marked by the many urban farming programs created by the Banjarbaru city government as well as the emergence of urban farming communities and business in Banjarbaru. However, the problem for the community is that there is no place for them to gather and spread information and education regarding the importance of urban farming to citizens. Therefore, it is necessary to design an urban farming educational park in Banjarbaru by implementing biophilic patterns by Terrapin Bright Green into the design so that users, the built environment and nature are connected and build positive interactions in the area.